2006
DOI: 10.4315/0362-028x-69.6.1240
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Escherichia coli O157:H7 Hide Contamination Routes: Feedlot to Harvest

Abstract: This study was conducted to identify the origin of Escherichia coli O157:H7 contamination on steer hides at the time of harvest. Samples were collected from the feedlot, transport trailers, and packing plant holding pens and from the colons and hides of feedlot steers. A total of 50 hide samples were positive for E. coli O157:H7 in two geographical locations: the Midwest (25 positive hides) and Southwest (25 positive hides). Hide samples were screened, and the presence of E. coli O157: H7 was confirmed. E. col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…The assumption has been made that a reduction in this fecal shedding by feedlot animals will lead to a reduced number of organisms on the hides of animals presented for processing and thereby a decrease in carcass contamination. However, there are several potential sources of E. coli O157:H7 contamination during the transport and lairage (e.g., animals shedding high numbers of E. coli O157:H7, trucks, lairage pens, alleys, chutes, and restrainers) that would seem to make further contamination likely (2,12). In one study, genetically similar isolates were obtained from the lairage environment surfaces and from cattle hides during processing (12), but cattle hides were not sampled at the feedlot to determine whether the organisms in question were present before transport.…”
mentioning
confidence: 99%
“…The assumption has been made that a reduction in this fecal shedding by feedlot animals will lead to a reduced number of organisms on the hides of animals presented for processing and thereby a decrease in carcass contamination. However, there are several potential sources of E. coli O157:H7 contamination during the transport and lairage (e.g., animals shedding high numbers of E. coli O157:H7, trucks, lairage pens, alleys, chutes, and restrainers) that would seem to make further contamination likely (2,12). In one study, genetically similar isolates were obtained from the lairage environment surfaces and from cattle hides during processing (12), but cattle hides were not sampled at the feedlot to determine whether the organisms in question were present before transport.…”
mentioning
confidence: 99%
“…Typically, this lot will have a shared diet and management regimen, and previous reports indicate that as a lot, cattle may share a predominant E. coli O157:H7 strain (16,17) in the feedlot environment. Our group and others (3,(18)(19)(20) have shown that upon arrival at the beef processing plant, the lairage environment can result in significant pathogen contamination of the cattle hide. This additional contamination adds many new strain types to the hide microflora, which may subsequently be transferred to the dehided carcass (3,7).…”
Section: Discussionmentioning
confidence: 90%
“…As cattle are placed in lairage at the processing plant, further contamination of the hide by E. coli O157:H7 occurs, which results in further increased strain diversity in the incoming load (3,19,20). This diversity can be observed in the hide sampling results presented in Table 3.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, manure and other animal waste management technologies must be put in place to contain pathogens in order to prevent or minimize human and animal exposures to them and thus the associated health risks [3,[24][25][26]. In fact, manures in most liarages should be routinely scraped and sold to landscapers and farmers as organic fertilizers [27]. By so doing, it would reduce the eyesore nature of the manure piles in these liarages in urban agglomerations as well as the chemical pollutants that can potentially contaminate surface and ground water systems [28][29][30].…”
Section: Microbial Propertiesmentioning
confidence: 99%